Synergistic effects of ultrasonic irradiation and PEG demulsifiers on oil-in-water emulsion separation - Mat Yajid, Nur Ainin Sofiya; Mat Shayuti, Muhammad Shafiq; Ghazali, Siti Aisyah; Tengku Mohd, Tengku Amran; Che Abdul Rahim, Azzah Nazihah; Mat Yusuf, Suriatie (Universiti Teknologi MARA Shah Alam, 2025)
A crude oil exporter like Malaysia continues to face challenges related to oil-in-water (O/W) emulsions. These emulsions are typically generated during extraction and transportation processes, leading to difficulties in effective separation. This study investigates the synergistic effects of ultrasonic irradiation and polyethylene glycol (PEG) 1500 demulsifiers on the separation efficiency of model diesel-based O/W emulsions. The emulsions were prepared using Tween 60 as a stabiliser, followed by treatments involving PEG 1500 and varying ultrasonic exposure for 5, 10, 30, and 60 s. A series of bottle tests and particle size analyses were conducted to evaluate demulsification performance and droplet size distribution. The findings revealed that the combination of ultrasonic treatment and PEG 1500 effectively enhanced emulsion destabilisation compared to chemical treatment alone. The optimal demulsification efficiency was achieved at 10 s of ultrasonic exposure (Sample D), which produced the highest oil separation percentage and the most balanced phase separation. However, prolonged irradiation beyond 30 s led to over-dispersion, droplet fragmentation, and reemulsification thereby reducing separation efficiency. The present particle size distribution results supported these finding where excessive ultrasonic irradiation yielded smaller and overly stable droplets resistant to coalescence.